The influence of bolts and shear connectors in the timber connection under compressive load - Indah Sulistyawati (Forest Research Institute Malaysia, 2015)
Three members of timber were jointed together with bolts as mechanical fasteners. Besides to joint the two members together, the function of the bolt is also prevent shear load between them when subjected to compressive load parallel to the length of members. The shear connectors were arranged and embedded at member interfaces in perpendicular direction to the timber grain. The share connectors are expected to enlarge, the bearing area which is equal to product of length multiplies with the diameter. Holes of about 1-mm oversize from the diameter of the bolts were made for ease of installation and to account for shrinkage. On the other hand,holes for shear connectors were made with the diameter being slightly smaller than its diameter. Acacia mangium lumber with Modolus Elasticity (MOE) of 10,000 MPa was used as timber members. The bolts were made from steel and has 10mm diameter with yield strength of 320 MPa and an Ultimate Tensile Strength of 460 MPa. The objective of the research is to evaluate the influences of connection system, two-bolts, a combination of bolt-shear connector and all bolts, on the compressive strength of the joints made from it. The study also evaluates the load-displacement for the characterization slope or equivalent axial stiffness (EA) eq and the ultimate load of member. The failure modes of the jointed members were assessed. The experimental results showed higher EA eq and lower value of ultimate loads in joints comprising a combination of bolts and shear connectors compare to other types of connectors used in the study.